A Case Study of Electronic Banking Operations at Meridian Bancorp - BANKER, R. D. (Institutional Knowledge at Singapore Management University, 1991)
The paper illustrates ‘business value linkage impact analysis’, a new method for measuring the business value of information technology (IT), in the context of a case study of electronic banking operations at Meridian Bancorp, a large commercial bank. Management science models were constructed to gauge the impact of automated teller machines (ATMs) on branch teller labour productivity and retail deposit market share, and the potential for substitution of labour by ATMs is shown. Econometric estimation of the models yielded the following results: the efficiency of teller labour was found to decline in the presence of a branch ATM; a bank's ATM network decision was shown to be an important determinant of the relative size of the retail deposit market it could capture in south-east Pennsylvania; membership in the regionally dominant MAC ATM network leveraged retail deposit market share when a clear majority of local branches and ATMs were members of a regionally smaller, competing network; and high-density ATM deployment did not lead to increases in the overall size of the deposit market.